ChemLotUS: A Benchmark Data Set of Lotic Chemistry Across US River Networks - N. Fernandez; M. J. Cohen; J. W. Jawitz (Water Resources Research)
Abstract We present a curated water chemistry data set for lotic systems across the contiguous US containing 35,000,000 records from 290,000 locations. These records are spatially joined to high‐resolution national hydrography data sets, providing information on watershed area, network position, and other hydrographic information. Our curation process follows best practices applied to raw query results from the Water Quality Portal, followed by assigning network context (position and watershed attributes) to each site from the high‐resolution National Hydrography Data set. The ChemLotUS data set currently includes 11 analytes selected to represent geogenic, biogenic, and anthropogenic processes: calcium, conductivity, pH, total suspended solids, turbidity, dissolved oxygen, total organic carbon, chlorophyll a, nitrate, soluble reactive phosphorus, and total phosphorus. All records from the raw query were modified during curation, most notably by removing duplicated observations, converting units, and aggregating strongly correlated chemical forms. Following curation, 65% of the original records were preserved, with significant reductions from raw to curated data in the means of nine constituents and, more notably, in the standard deviations of all constituents. 95% of monitored river reaches were linked to three or fewer monitoring sites, with sample patterns revealing a strong measurement bias to high order streams. We demonstrate the functionality of ChemLotUS by identifying spatiotemporal patterns in water quality at the CONUS‐scale, including diurnal variations of dissolved oxygen, pH in headwaters compared to their corresponding river mouths, and total suspended solids as a function of stream order. ChemLotUS enables new opportunities for investigations of continental scale variation in and controls on water quality.